FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN MINUMAN JAMUGENDONG DI SURAKARTA - Saptani Rahayu (BHIRAWA, 2015)
The aim of this study is to analyze the factors influencing the Customer Loyalty Hold herbs in Surakarta, with a sample of 100 customers carrying medicinal. Analysis of data using multiple regression, t test, F test and coefficient of determination. While the results of multiple regression hypothesis testing is Tangible, reliability, responsiveness, assurance, empathy, have positive effect on customer loyalty. T test results showed that tangible, reliability, responsiveness, assurance, empathy and job satisfaction as independent variables significantly influence customer loyalty carrying medicinal in Surakarta. The test results are known magnitude F F value of 203.913 and a significance value of 0.000